Annual Plan 1993-94 Volume-IV General Areas Government of Assam - Planning Commission (Planning Commission, 1993)
The approved outlays under Annual plan 1992-93 for General Areas is Rs. 3872.00 Lakhs of which Rs. 425.00 Lakhs is fixed for MNP Rural Roads) . The physical Target is 136 Kms. of surfaced Roads and 378 Kms. of un-surfaced Roads, it is expected that the targets both under physical and Financial will be achieved in full.
Government of Assam, Planning and Development Department